Metacognition-based learning materials in grade 9 science - Petero, Milani C. (Virgen Milagrosa University Foundation : [s.n.], 2018)
This study aimed to develop and evaluate metacognition-based learning materials in Grade 9 Science. It determined the degree of need for metacognition- based learning materials in Grade 9 Science; the description of the metacognition-based learning materials in terms of objectives, presentation of concepts and activities or exercises; the acceptability of the learning activities or exercises in promoting metacognition and validity of the learning materials as rated by experts (content, instructional materials and information & communication technology). The quantitative-descriptive and developmental method of research design was used in the development of metacognition-based learning materials in Grade 9 Science. The content of the learning materials was based on the competencies given in the K to 12 Science curriculum guide. It covered three topics, namely: chemical bonding, organic compounds and mole concept. The researcher found out that there is an urgent need for metacognition- based learning materials in Grade 9 Science. The experts rated the activities / exercises in the learning materials as highly acceptable in promoting metacognition among Grade 9 learners. On the validity of the learning materials, experts evaluated in terms of objectives, format, content, organization, language and usability. The experts found the metacognition-based learning materials in Grade 9 Science as, highly valid. The experts' comments and suggestions were incorporated in the learning materials.
Bibliography: pages 277-281.
CHED-La Union
Keywords: Teaching -- Aids and devices